Impact of Hybrid Varieties on the Productivity of Rice Cultivation: The Case of Sindh, Pakistan - Abbasi, Saqib (Jordan Journal of Agricultural Sciences, 2024)
Agriculture is a very important sector and crucial for poverty reduction and employment generation. The use of hybrid seeds leading to increased yield of crops and farmers’ income has been widely discussed in the literature. Through this study, an effort has been made to identify factors that impact obtaining high crop yield of rice by using the hybrid varieties. This study focuses on the use of hybrid varieties in the rice crop and presents a comparison in yield with the traditional open-pollinated varieties. The plot level information collected from eight major rice-producing districts of Sindh province of Pakistan was used to conduct this study and a propensity score matching technique was used to estimate the results of the study by using plot level variation between hybrid varieties and open-pollinated varieties. The results of the study showed significant improvement in rice yield with the adoption of hybrid rice varieties in the study area. This study highlights that the farmers have achieved a higher average yield of rice by using hybrid seeds as compared to open-pollinated varieties. Besides the crop yield, the overall income and profit of farmers have also increased by using hybrid seeds in the Sindh province. The study illustrates different interesting patterns relating to different characteristics of the household cultivating rice crops, different plot-level characteristics, and their comparison with hybrid and traditional varieties.